Natriuria and calciuria levels in preeclampsia: a cross-sectional study - Gasnier, Rose; Valério, Edimárlei Gonsales; Vettorazzi, Janete; Martins-Costa, Sérgio Hoffmeister; Barros, Elvino Guardão; Ramos, José Geraldo Lopes (São Paulo Medical Journal, 2013)
CONTEXT AND OBJECTIVE: Sodium excretion abnormalities in preeclampsia have been studied in relation to several factors. The objective of this study was to compare natriuria (mEq/24 h) and calciuria levels (mg/24 h) in preeclamptic patients. DESIGN AND SETTING: An analytical cross-sectional study with a control group was conducted in the obstetric center and the high-risk pregnancy outpatient clinic at a university hospital in southern Brazil, and in a primary healthcare unit in the same city, including pregnant women with mild preeclampsia, severe preeclampsia or chronic hypertension, and women with normal pregnancies (14 patients in each group). METHOD: Natriuria was measured using an ion-selective electrode in an automated clinical chemistry analyzer (Hitache 917, Roche). All the patients collected 24-hour urine, at home or at the hospital, for analysis of proteins, creatinine, calcium, sodium and uric acid. Quantitative variables with asymmetrical distribution were described using the median, minimum and maximum, and were compared using the Kruskal-Wallis test. The results were logarithmically transformed, with one-way analysis of variance (ANOVA) by ranks and then the post-hoc Tukey test, and were analyzed by means of the Spearman correlation and receiver operating characteristic (ROC) curve. The significance level used was 0.05. RESULTS: There were significant differences between the groups in comparing severe preeclampsia with chronic hypertension and severe preeclampsia with controls (P < 0.0001 for both measurements). CONCLUSION: Natriuria levels may be lower in preeclampsia when associated with calciuria. Natriuria assessment is an additional test for differential diagnosis of hypertensive diseases in pregnancy, but is a poor predictor when used alone.